Effect of Nitridation on High Temperature Corrosion of Ferritic Stainless Steel - Bergamo, Tiziano (My University, 2013)
The emission of nitrogen monoxide in the atmosphere is one of the main causes of air pollution. In this regards, the truck industry introduced the Selective Catalytic Reduction (SCR) in exhaust after-treatment system of heavy-duty trucks. Through the use of urea water solution injected into the gas flow, NOx can be reduced to N2 and H2O. The high temperatures in the exhaust system, together with the products of the reduction reactions, produce a particularly corrosive environment, strongly detrimental for the corrosion resistance of the stainless steels used. The aim of this work was to evaluate the effect of nitridation on the oxidation resistance of AISI 444 ferritic stainless steel. The oxidation of both as-received and nitrided 444 coupons in the presence of 10% H2O was investigated in the temperature range of 450 and 600°C. The exposure time was between 24 and 168 hours. The samples were characterized by using several techniques including LOM, SEM, EDS, XPS, XRD. An expanded ferrite phase supersaturated with nitrogen was formed on the surface of 444 ferritic stainless steel after plasma nitriding at about 400°C. The layer thicknesses were about 10-20 μm with a nitrogen atomic content of about 15-13%. The detrimental effect of nitridation was very strong on the oxidation resistance of ferritic 444. The oxide scales formed on nitrided samples were 50-100 times thicker than on as-received samples. The lower chromium activity in nitrided 444 due to formation of short-range ordering with nitrogen decreases the chromium diffusion toward the surface and hinders formation of protective oxides. The oxidation on 444 ferritic stainless steel definitely decreased with increasing temperatures, although the larger formation of Cr-nitrides at higher temperatures. The increase of chromium diffusion due both to higher temperatures and larger leak of nitrogen from the expanded ferritic phase improves the oxidation resistance of the ferritic 444. The oxidation resistance in presence of 10% H2O at 450-600°C seems better for nitrided 444 ferritic stainless steel than for nitrided 304L austenitic stainless steel investigated in previous studies.
Keywords: Korrosionsteknik; Hållbar utveckling; Materialteknik; Konstruktionsmaterial; Materialvetenskap; Corrosion Engineering; Sustainable Development; Materials Engineering; Construction materials; Materials Science